Determinação da disponibilidade de Ca, Cu, Fe, Mg e Zn em amostras de carnes bovinas, suínas e de frango In natura e processadas termicamente - Menezes, Eveline de Abreu (2010)
In this work, the availability of Ca, Cu, Fe, Mg, and Zn in bovine, pork and chicken meat samples raw and after thermal treatments: water boiled, grilled, microwave, convention oven I 180 oC (FCI) and conventional oven II 60 min and 180 oC was evaluated. Total determination of Ca, Cu, Fe, Mg and Zn in bovine and pork samples was performed by inductively coupled plasma optical emission spectrometry (ICP OES), and Cu in chicken samples was determined by graphite furnace atomic absorption spectrometry (GFAAS), after digestion assisted by microwave radiation. Total protein determination was performed based on total nitrogen determination and the protein digestibility determination was determined by using the method proposed by Akeson and Stahman, in which the sample is digested with digestive enzymes in an acidic medium, simulanting in vitro conditions. To the mineral availability evaluation, an in vitro procedure, simulated gastric fluid was applied. Independent of the procedure of cooking, similar behavior was observed for all meat sample evaluated. Increasing temperature and exposition time of food to heat, decreases in proteins availability was observed, probably due to proteins denaturation. The bovine meat presented about 20% of Cu, Fe, and Zn availability, that became this kind of food an important source of these nutrients in human nutrition. When the meat was water boiled, it was observed increase in nutrients availability. For all samples, the use of conventional oven during 60 min at 180oC (FCII) presented reduces in nutrients and proteins availability, indicating that this thermal treatment can change the digestibility and mineral absorption of the evaluated meat samples.